Trends in the Incidence of Young-Onset Colorectal Cancer With a Focus on Years Approaching Screening Age: A Population-Based Longitudinal Study. (25th January 2021) - Howren, Alyssa; Sayre, Eric C; Loree, Jonathan M; Gill, Sharlene; Brown, Carl J; Raval, Manoj J; Farooq, Ameer; De Vera, Mary A.
Abstract: Background: With recent evidence for the increasing risk of young-onset colorectal cancer (yCRC),  we had the objective to evaluate the incidence of yCRC in 1-year age increments, particularly focusing around the screening age of 50 years. Methods: We conducted a longitudinal study using linked administrative health databases in British Columbia, Canada, including a provincial cancer registry, inpatient and outpatient visits, and vital statistics from January 1, 1986, to December 31, 2016. We calculated incidence rates per 100 000 at every age from 20 to 60 years and estimated annual percent change in incidence (APCi) of yCRC using joinpoint regression analysis. Results: We identified 3614 individuals with yCRC (49.9% women). The incidence of CRC steadily increased from 20 to 60 years, with a marked increase from 49 to 50 years (incidence rate ratio = 1.19, 95% confidence interval [CI] = 1.04 to 1.34). Furthermore, there was a trend of increased incidence of yCRC among women (APCi = 0.79%, 95% CI = 0.22% to 1.36%) and men (APCi = 2.17%, 95% CI = 1.59% to 2.76%). Analyses stratified by age yielded APCis of 2.49% (95% CI = 1.36% to 3.63%) and 0.12% (95% CI = −0.54% to 0.79%) for women aged 30-39 years and 40-49 years, respectively, and 2.97% (95% CI = 1.65% to 4.31%) and 1.86% (95% CI = 1.19% to 2.53%) for men. Conclusions: Our findings indicate a steady increase over 1-year age increments in the risk of yCRC during the years approaching and beyond screening age. These findings highlight the need to raise awareness as well as continue discussions regarding considerations of lowering the screening age.